The network effects of NGOs on social capital and innovation among smallholder farmers - Hartmann, Dominik (2023)
Hartmann, D., Arata, A., Bezerra, M., & Pinheiro, F. L. (2023). The network effects of NGOs on social capital and innovation among smallholder farmers: a case study in Peru. Annals Of Regional Science, 70(3), 633-658. https://doi.org/10.2139/ssrn.3312468, https://doi.org/10.1007/s00168-019-00944-9--- %ABS2%---DH expresses his gratitude for the financial support of the São Paulo Research Foundation (PROCESSO 2017/19842-2) as visiting scholar at the University of São Paulo. AA would like to express his gratitude for the collaboration of the Center for Studies and Promotion of Development (DESCO)